Palace of Mirrors - Haddix, Margaret Peterson (New York : Simon & Schuster Books for Young Readers, 2008)
Fourteen-year-old Cecilia has always known she is the true princess of Suala, but when she and her best friend, Harper, decide to speed up her ascendancy to the throne, they find danger and many imposters who challenge her claim.
Accelerated Reader AR